Find_Me: IoT indoor guidance system - Martinho, S. (2018)
This work presents an approach to combine location information from beacons and local building information to give real time location and guidance to a user inside a building. This information can help users orientation inside unknown buildings and the data stored from different users can provide useful information about users movements inside public building. Beacons are installed on the building and emit signals that give a geographic position with an associated imprecision, related with Bluetooth’s range. This uncertainty is handle by building layout and users’ movement in a developed system that maps users position, gives guidance and store user movements. This system is based on a App (Find Me!) for Android OS (Operating System) which captures the Bluetooth Low Energy (BLE) signal coming from the beacon(s) and shows, through a map, the location of the user ‘s smart phone and guide him to the desired destination